Complete Genome Sequence of Xylella taiwanensis and Comparative Analysis of Virulence Gene Content With Xylella fastidiosa - Weng, Ling-Wei; Lin, Yu-Chen; Su, Chiou-Chu; Huang, Ching-Ting; Cho, Shu-Ting; Chen, Ai-Ping; Chou, Shu-Jen; Tsai, Chi-Wei; Kuo, Chih-Horng (Frontiers in Microbiology, 2021)
The bacterial genus Xylella contains plant pathogens that are major threats to agriculture in America and Europe. Although extensive research was conducted to characterize different subspecies of Xylella fastidiosa (Xf), comparative analysis at above-species levels was lacking due to the unavailability of appropriate data sets. Recently, a bacterium that causes pear leaf scorch (PLS) in Taiwan was described as the second Xylella species (i.e., Xylella taiwanensis; Xt). In this work, we report the complete genome sequence of Xt type strain PLS229T. The genome-scale phylogeny provided strong support that Xf subspecies pauca (Xfp) is the basal lineage of this species and Xylella was derived from the paraphyletic genus Xanthomonas. Quantification of genomic divergence indicated that different Xf subspecies share ~87-95% of their chromosomal segments, while the two Xylella species share only ~66-70%. Analysis of overall gene content suggested that Xt is most similar to Xf subspecies sandyi (Xfs). Based on the existing knowledge of Xf virulence genes, the homolog distribution among 28 Xylella representatives was examined. Among the 11 functional categories, those involved in secretion and metabolism are the most conserved ones with no copy number variation. In contrast, several genes related to adhesins, hydrolytic enzymes, and toxin-antitoxin systems are highly variable in their copy numbers. Those virulence genes with high levels of conservation or variation may be promising candidates for future studies. In summary, the new genome sequence and analysis reported in this work contributed to the study of several important pathogens in the family Xanthomonadaceae.